Geography and Migration Studies: Retrospect and Prospect - King, Russell (Population space and place, 2012)
ABSTRACT The paper engages with migration theory through a geographic perspective. It first argues that geographers, with their broad‐ranging subject matter, epistemological pluralism, and varied research methods, are ideally placed to carry out migration research and advance migration theory. Second, the paper casts a retrospective view at some highlights of geographers' theoretical contributions to migration. The third part reviews the recent and current states of play, which have seen a shift in the geographical study of migration from population geography to cultural geography, via the ‘cultural turn’. Four paradigmatic trends in the study of migration are reviewed – the mobilities turn, transnationalism, diaspora studies, and gendered approaches – and geographers' contributions to each of these are evaluated. The conclusion looks to the future, asks whether the cultural turn is over and, in the light of the global economic crisis, identifies new avenues of migration research for migration geographers. Copyright © 2011 John Wiley & Sons, Ltd.